Risk factors for fragility fractures in patients with immunobullous diseases on long-term systemic glucocorticoids - MeiQi May Liau; Nisha Suyien Chandran (PAGEPress Publications, 2024)
Dear Editor, Systemic glucocorticoids remain a cornerstone of therapy in immunobullous diseases. Yet little is known about glucocorticoid induced osteoporosis (GIOP) in patients with immunobullous diseases. We performed a retrospective review of medical records at an immunodermatology clinic in a Singaporean tertiary centre. Inclusion criteria consisted of patients with a newly diagnosed immunobullous condition between January 2011 and October 2017, who were on long-term (>= 3 months) systemic glucocorticoids at a minimum daily dose of prednisolone 15mg. [...]